Contrast-induced kidney injury: how does it affect long-term cardiac mortality?. Issue 11 (November 2017) - Andreis, Alessandro; Budano, Carlo; Levis, Mario; Garrone, Paolo; Usmiani, Tullio; D'Ascenzo, Fabrizio; De Filippo, Ovidio; D'Amico, Maurizio; Bergamasco, Laura; Biancone, Luigi; Marra, Sebastiano; Colombo, Antonio; et al.
Abstract : Aims: Contrast-induced acute kidney injury (CIAKI) is a common complication after coronary angiography or percutaneous revascularization (PCI). This study aimed to investigate the association of CIAKI with long-term cardiovascular adverse events. Methods: In total, 980 patients undergoing coronary angiography/PCI were assessed in this prospective cohort study. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE) and cardiac death (CVD) during an 8-year follow-up. Glomerular filtration rate change during the follow-up was the secondary endpoint. CIAKI was defined as a serum creatinine increase at least 0.3 mg/dl in 48 h or at least 50% in 7 days. Results: CIAKI was observed in 69 patients (7%). Chronic kidney disease [relative risk (RR) = 4, P < 0.01], reduced ejection fraction (RR = 2.88, P < 0.01), CIAKI risk score at least 4 (RR = 2.64, P = 0.02), and emergency coronary angiography/PCI (RR = 3.87, P < 0.01) increased CIAKI risk, whereas statins were protective (RR = 0.32, P < 0.01). Patients with CIAKI had higher rates of 8-year cardiovascular adverse events: 54 versus 15% MACCE (RR = 6.67, P < 0.01), 38 versus 4% CVD (RR = 15.73, P < 0.01). Among other factors, CIAKI was the strongest predictor of 8-year MACCE (RR = 3.16, P < 0.01) and CVD (RR = 7.34, P < 0.01). During the follow-up, glomerular filtration rate declined drastically in CIAKI patients: 70 versus 39% had chronic kidney disease stage worsening ( P < 0.01) and 8 versus 0.3% started hemodialysis ( P < 0.01). Conclusion: We found a strong correlation between CIAKI and poor long-term cardiac outcomes. Apparently showing up as a transient, functional impairment of kidney function, CIAKI implies an organic damage with structural modifications leading to significant kidney deterioration over time, responsible for an increased risk of long-term cardiac events. Statins significantly reduced CIAKI occurrence. A careful management of high-risk patients is needed to limit long-term complications of coronary angiography/PCI.